Composição da avifauna do Parque Ecológico e Cultural “Gilberto Ruegger Ometto”, município de Araras-SP - Rodrigues, Ianca Lima (Universidade Federal de São Carlos, 2025)
Birds are vital components of ecosystems, serving functions such as pollination, seed dispersal, predation and acting as bioindicators of environmental health. However, urbanization and habitat fragmentation exert detrimental impacts on avian populations, leading to reduced biodiversity and modified community structures. In this context, urban green spaces, particularly parks, are increasingly important as refuges for wildlife, underscoring the importance of research aimed at characterizing avian assemblages within urban ecosystems. The present study aimed to conduct a qualitative survey of the avifauna in the “Gilberto Ruegger Ometto” Ecological and Cultural Park, located in the municipality of Araras-SP, to identify the bird species present, their feeding guilds, and potential relationships with local environmental characteristics. The study area comprises lakes, marginal vegetation, open spaces, and wooded areas, all within an urban setting. Data collection was conducted between September 2024 and March 2025, utilizing linear transect and fixed-point methods, and encompassing both visual and auditory observations. A total of 83 bird species were recorded, distributed among 37 families and 16 orders, with Passeriformes being the most representative. The analysis of feeding guilds indicated a predominance of insectivores, carnivores and omnivores. In addition, the presence of several species nesting and foraging in the site reinforces its ecological relevance for urban avifauna. The high frequency of generalist species adapted to modified environments, such as those from the Tyrannidae and Thraupidae families, confirms patterns already recorded in other urban areas of the state. The study highlights the importance of urban green areas as functional refuges for birds, highlighting the need for conservation and adequate management of these spaces to maintain local biodiversity. Keywords: urban
Composition of the birds of the “Gilberto Ruegger Ometto” Ecological and Cultural Park, Araras, SP
Keywords: Avifauna Urbana; Guildas alimentares; Parque urbano; Urban avifauna; Feeding guilds; Urban park; CIENCIAS BIOLOGICAS::ECOLOGIA